Optimization of Legal Protection for Workers Against Invalid Contracts in Employment Law - Sofhuan Yusfiansyah; Richard, Richard (Jurnal Multidisiplin Indonesia, 2025)
Legal protection for workers is a crucial aspect of employment law to ensure welfare and job security. However, in practice, there are still many invalid employment contracts that conflict with laws and regulations, such as the misuse of Fixed-Term Employment Agreements (PKWT) that exceed the specified time limit, fictitious contracts, and agreements that do not provide legal certainty for workers. This study aims to analyze the forms of employment contracts that conflict with employment law and the obstacles to legal protection for workers. This study uses a normative legal method with a statutory approach and an analytical approach focuses on the analysis of Law Number 6 of 2023 concerning Job Creation, Law Number 13 of 2003 concerning Manpower, and other related regulations. The results show that weak supervision, low understanding of workers’ rights, and the difficulty of the dispute resolution process are the main factors that hinder legal protection for workers against invalid employment contracts. Therefore, it is necessary to optimize policies and enforce stricter laws so that workers’ rights can be protected effectively.